1977
DOI: 10.1080/03015521.1977.10425970
|View full text |Cite
|
Sign up to set email alerts
|

Survey of paspalum in New Zealand pastures

Abstract: A survey was undertaken among farm advisory officers of the Ministry of Agriculture and Fisheries to determine the distribution of, production from, and attitudes to Paspalum dilatatum in New Zealand. Paspalum is widespread throughout most of Northland, Auckland. Bay of Plenty, Waikato, and Poverty Bay. It is present in most of the remainder of the North Island and in northwestern South Island. Abundance is decreasing in Northland and is static in most other districts except Waikato where some increase was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…By 1974 paspalum was widespread in Northland, Auckland, Waikato, Bay of Plenty and Poverty Bay, was present in most of the rest of the North Island and was also in northwestern South Island (Percival 1977). A survey reported by Field & Forde (1990) suggested that many C 4 grasses were spreading aggressively under the influence of favourable climate.…”
Section: Forage Grasses In New Zealandmentioning
confidence: 99%
“…By 1974 paspalum was widespread in Northland, Auckland, Waikato, Bay of Plenty and Poverty Bay, was present in most of the rest of the North Island and was also in northwestern South Island (Percival 1977). A survey reported by Field & Forde (1990) suggested that many C 4 grasses were spreading aggressively under the influence of favourable climate.…”
Section: Forage Grasses In New Zealandmentioning
confidence: 99%
“…is a subtropical pasture species distributed throughout most of Northland, Auckland, Bay of Plenty, Waikato, and Poverty Bay (Percival 1977), and has desirable water utilisation properties during dry periods (Lambert 1967). Comparisons under grazing and mowing indicated that grazing severely depressed paspalum productivity and that most other pasture grasses produced almost as' much under grazing as under mowing (Lambert 1967).…”
Section: Introductionmentioning
confidence: 99%
“…), a drought tolerant, perennial, subtropical grass, is an important summer component of many pastures in the northern half of the North Island (Percival 1977). It also frequently occurs in lawns and on roadsides.…”
Section: Introductionmentioning
confidence: 99%